Impact of phacoemulsification parameters on central retinal thickness change following cataract surgery - Mackenbrock, Lars; Baur, Isabella; Łabuz, Grzegorz; Auffarth, Gerd U.; Khoramnia, Ramin (Diagnostics, 2023)
Cataract surgery can lead to inflammatory processes in the retina due to its invasive nature, resulting in prolonged recovery times and reduced functional outcomes. The aim of the current study is to explore the impact that phacoemulsification parameters have on macular thickness following surgery. This prospective single-center study enrolled 46 healthy patients (46 eyes) who underwent uneventful cataract surgery. Retinal thickness was assessed using optical coherence tomography (OCT) preoperatively, as well as 1, 4, and 12 weeks after surgery. The macula was divided into a central (CMT), inner (IMT), and outer ring (OMT). Cataract density was automatically determined using an anterior segment OCT and a custom MATLAB script. Corrected distance visual acuity (CDVA), intraocular pressure (IOP) as well as cumulative dissipated energy (CDE), ultrasound time (UT), and fluids used during phacoemulsification were recorded. Retinal thickness and volume increased significantly following cataract surgery, reaching its maximum 4 weeks post-operatively. Statistically significant correlations were found between the CDE and IMT, OMT and retinal volume change (rIMT = 0.356, rOMT = 0.298, rvolume = 0.357 with p < 0.05) as well as between the ultrasound time and IMT, OMT, and retinal volume change (rIMT = 0.369, rOMT = 0.293 and rvolume = 0.409 with p < 0.05). Changes in CMT did not correlate with any surgical metrics. Additionally, no correlation was found to the amount of fluid used, whether CDVA or IOP. However, a link between nuclear cataract density and changes in OMT (r = 0.310, p < 0.05) was established. How ultrasound energy impacts the choroidea, and to what extent retinal metabolism changes after surgery, needs to be explored in future studies.
Veröffentlicht: 4. September 2023
Gesehen am 16.10.2023